Method for treating a part made of an iron alloy to improve its corrosion protection properties

The method of nitriding iron alloy parts in a chloride-containing molten salt bath and subsequent phosphorylation in a zinc, manganese, and iron ion bath addresses the cost and complexity issues of existing treatments, achieving effective corrosion resistance and mechanical strength without degraphitization.

JP2025509652APending Publication Date: 2025-04-11CENT STEPHANOIS DE RECH MECANIQUES HIDROMECANIQUE & FROTTEMENT
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024554939
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-14
Filing Date
2023-01-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing methods for treating iron alloy parts, such as grey cast iron, to improve corrosion resistance and mechanical strength are costly and complex, often requiring degraphitization and precise control of sulfur species during nitriding.

Method used

A method involving nitriding in a molten salt bath containing chloride ions, followed by phosphorylation in a bath with zinc, manganese, and iron ions, without the need for degraphitization, to form a nitride layer and a phosphorylated layer that enhances corrosion resistance and mechanical strength.

Benefits of technology

This method reduces production costs and time while maintaining excellent hardness, wear resistance, and corrosion resistance properties, making it suitable for applications like brake discs without the need for degraphitization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509652000001_ABST
    Figure 2025509652000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for treating a part (P) made of an iron alloy in order to improve its corrosion protection and mechanical strength properties, comprising the steps of: - forming a mixed layer (1) on the part (P) by salt bath nitriding or salt bath nitrocarburizing, and then - phosphating the component to form a phosphating layer (2) on the surface of the component; Including, The bath of molten salt contains chlorides; The method is characterized in that the phosphating step is carried out in a phosphating bath containing zinc and / or manganese ions, as well as iron ions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for treating parts made of iron alloys by nitriding and phosphating in order to improve their corrosion protection properties, and to parts made of iron alloys treated by nitriding and phosphating. [Background technology]

[0002] In automotive, aeronautical or industrial applications, mechanical components are typically subjected to significant operational stresses.

[0003] Conventionally, mechanical parts may be subjected to one or more treatments making it possible to improve some of their performance properties, among them the frictional properties, the wear resistance, the fatigue resistance or even the corrosion resistance.

[0004] Among these various treatments, nitriding is an interesting option: it consists of immersing a part made of ferrous metal in a medium capable of donating nitrogen, the formation of iron nitrides on the surface of the part and the diffusion of nitrogen from the surface to the core of the part resulting in a significant surface hardening.

[0005] Nitriding includes nitrocarburizing, which is a variation of nitriding where carbon is infiltrated into the component in addition to nitrogen. The ARCOR process described later in this specification, developed by the applicant and practiced for many years, is a preferred example of a nitrocarburizing process. In the remainder of this specification, both nitriding and nitrocarburizing are combined under the single term "nitriding".

[0006] Nitridation can be carried out from the gas, plasma, or liquid phase.

[0007] Liquid phase nitriding, also called salt bath nitriding, has the advantage that it allows significant hardening over a thickness of tens of microns in just a few hours, making it the first choice. The bath of molten salts is typically at a temperature of about 600° C. and contains in practice cyanates and carbonates, as well as cations, usually alkali metal cations such as lithium, sodium or even potassium.

[0008] Nitriding makes it possible to harden the surface of the component and therefore improve its wear resistance. Nitriding may also improve the sliding and gripping properties.

[0009] Nitriding is often combined with other treatments, for example when good corrosion resistance is required.

[0010] For example, phosphating is such a treatment, which makes it possible to improve the performance of the parts in terms of corrosion resistance.

[0011] The performance of a component subjected to phosphating, regardless of its application, depends primarily on two features: the crystallinity of the phosphating layer and the quality of its adhesion onto the substrate.

[0012] It is therefore generally desired to obtain a fine and regular crystallization during the phosphorylation step, which results in a phosphorylation layer that is as dense as possible.

[0013] These two features depend directly on the quality of the metal surface preparation of the substrate, strictly speaking, prior to the phosphating step: the physicochemical state of this surface actually conditions its reactivity towards the activators of the phosphating bath and the growth of the phosphorylated composite layer.

[0014] By implication, the part may be cleaned, degreased and dried prior to the nitriding and / or phosphating steps. These conventional steps do not modify the chemistry of the part being treated or its structure. However, in certain cases, other pretreatment steps are practiced.

[0015] It is therefore known to those skilled in the art that the crystallinity of the phosphate layer can be improved by a pretreatment consisting of depositing a finely dispersed titanium compound on the surface to be phosphating. The applicant has also demonstrated in patent EP 0 560 641 that phosphating can be accelerated and a fine crystallinity ensured by nitriding in the presence of sulfur species.

[0016] However, the content of sulfur species must be low (around 10 ppm), and controlling and maintaining good content of sulfur species increases the complexity and cost of such nitridation.

[0017] Thus, costs can be high for processing inexpensive materials such as ultra-low alloy steels or cast iron.

[0018] In the specific case of cast iron, grey cast iron is a cast iron in which carbon crystallizes in the form of graphite inclusions that can take the form of long and thin graphite lamellae, nodules (spheroids) or vermicular. These inclusions, when released on the surface of the part, can disrupt the surface treatment and thus form primer points for corrosion. It has therefore been proposed to carry out a degraphitization treatment before nitriding in order to improve the corrosion resistance (described in document WO2016143712). However, such a pretreatment also increases the duration and overall cost of the treatment of grey cast iron.

[0019] Lamellar cast iron, whose inclusions are in the form of lamellae, has the advantage of being cheaper than other cast irons. Spheroidal cast iron requires the addition of crystallizing elements (rare earths, lithium, magnesium), which increases its cost.

[0020] In general, grey cast iron is a very inexpensive material, but is somewhat difficult to protect from corrosion.

[0021] Gray cast iron is used to manufacture brake discs for automobiles, since it is a cheap material. Often, brake discs are not treated and have very low corrosion resistance. During braking, the corrosive attack on the disc surface is worn away by the platelets and thus removed.

[0022] However, with the advent of electric vehicles and electrical energy recovery during braking, mechanical brakes are less stressed and possible corrosive attack present on the surface of the disc is now not eliminated, leading to unsightly and braking quality impairing corrosion spreading over the entire brake disc.

[0023] Furthermore, if the vehicle is stored for an extended period of time prior to sale, the presence of unsightly corrosion on the brake discs can detract from the appearance of the vehicle and deter a purchaser.

[0024] Therefore, inexpensive but corrosion-resistant machine parts should be proposed, especially brake discs, where phosphorylation alone is not sufficient, since the phosphorylation layer is removed during the first braking. [Prior art documents] [Patent documents]

[0025] [Patent Document 1] European Patent No. 0560641 [Patent Document 2] International Publication No. 2016 / 143712 [Patent Document 3] French Patent Application Publication No. 2972459 [Patent Document 4] French Patent Application Publication No. 2812888 Summary of the Invention [Problem to be solved by the invention]

[0026] Faced with this situation, the Applicant sought a solution to simplify the method of treating mechanical parts by nitriding and subsequent phosphating, quite specifically in view of the surface preparation constraints prior to the phosphating step, which, precisely speaking, increase the production costs.

[0027] The method should preferably be adapted to process grey cast iron despite the inherent limitations of this material, but it should be possible to apply the method to any cast iron or low alloy steel, and in theory to all iron alloys. [Means for solving the problem]

[0028] For this purpose, the invention relates to a method for treating a part made of an iron alloy in order to improve its corrosion protection and mechanical strength properties, comprising the steps of: - forming a mixed layer on the part by molten salt bath nitriding or molten salt bath nitrocarburizing; - phosphating the component to form a phosphating layer on the surface of the component; In a method comprising: Essentially, a process is proposed which is characterized in that the bath of molten salt contains chlorides and the phosphating step is carried out in a phosphating bath which contains zinc and / or manganese ions, as well as iron ions.

[0029] Applicant is not aware of the presence of chloride (i.e., Cl - It has been noticed that by carrying out a nitriding step in the presence of chloride ions (and thus species containing chloride ions such as chlorine salts) and a subsequent phosphating step with zinc and iron (of the zinc / iron, Zn / Fe type), or manganese and iron (of the manganese / iron, Mn / Fe type), or zinc and manganese and iron (of the zinc / manganese / iron, Zn / Mn / Fe type), it is possible to obtain parts with good corrosion protection and good mechanical strength properties.

[0030] Moreover, in the specific case of parts made of grey cast iron, the method of the invention not only results in the above-mentioned advantageous mechanical properties, in particular mechanical strength relatively similar to the current standard for grey cast iron, i.e. nitriding and subsequent gas phase oxidation, but also makes it possible to avoid prior degraphitization. In applications requiring a low coefficient of friction, zinc can be at least partially replaced by manganese.

[0031] Conversely, if it is desired to maintain a relatively high coefficient of friction, for example in brake discs, the presence of manganese ions in the phosphating bath should therefore be avoided.

[0032] Therefore, the phosphorylation bath is a normal PO 4 3- In addition to phosphate ions, Zn 2+ Zinc ions and / or Mn 2+Manganese ions, and Fe 2+ Contains iron ions.

[0033] As mentioned above, the method of treating a component according to the invention does not include any step of degraphitizing the component prior to phosphating, i.e. prior to phosphating or even prior to nitriding.

[0034] The absence of degraphitization makes it possible to reduce time and production costs without compromising the quality of the parts obtained, in particular their good hardness, wear and corrosion resistance properties.

[0035] The method according to the invention is therefore advantageously applied to, but not limited to, ferrous alloy parts, particularly grey cast iron parts, which normally require degraphitization.

[0036] According to other aspects, the treatment method according to the invention has the following different characteristics, taken individually or in any technically possible combination: - the bath of molten salt does not contain sulfur; - the chlorides include alkali metal chlorides; the alkali metal chloride is lithium chloride, sodium chloride and / or potassium chloride; - Molten salt bath CNO - Cyanate ion, (CO 3 ) 2- Carbonate ion, and preferably Li + Lithium ion and / or K + Potassium ion and / or Na + containing an alkali ion selected from among sodium ions; - The molten salt bath for nitriding 25% to 60% alkali metal chlorides, 10% to 40% alkali metal carbonate, 20% to 50% alkali metal cyanate, Less than 3% cyanide ion , where the percentage is expressed by weight relative to the total weight of the bath; - The content of zinc, manganese and iron ions in the phosphating bath is adjusted according to the alloy of the parts to be treated and the expected performance as follows: If the phosphating bath contains zinc ions but no manganese ions, said zinc ions are present in a mass concentration of 1 g / l to 40 g / l (grams per liter), preferably 5 g / l to 20 g / l, relative to the total volume of the phosphating bath; If the phosphating bath contains manganese ions but no zinc ions, said manganese ions are present in a mass concentration of 1 g / l to 40 g / l, preferably 5 g / l to 20 g / l relative to the total volume of the phosphating bath; If the phosphating bath contains zinc and manganese ions, the sum of these ions is present in a mass concentration of 1 g / l to 40 g / l, preferably 5 g / l to 20 g / l. Additionally and optionally, manganese ions may constitute 10% to 90% by weight, preferably 25% to 75% by weight, advantageously 40% to 60% by weight of the total mass of zinc and manganese ions; The iron ions are in each case present in the phosphating bath in a mass concentration of 1 g / l to 8 g / l, preferably of 1 g / l to 6 g / l and more preferably of 1 g / l to 5 g / l; The bath optionally contains nitric acid or a nitrate; The remainder of the bath is made up primarily of water. - the phosphorylation layer has a thickness of between 3 μm and 40 μm, preferably between 5 μm and 30 μm, even more preferably between 5 μm and 20 μm; - the mixed layer has a thickness dimension of 5 μm to 40 μm, preferably 15 μm to 25 μm; - The parts are made of grey cast iron.

[0037] The method of the invention applies very particularly to brake discs, when the phosphating bath does not contain manganese ions.The invention therefore also relates to a method for treating a part made of grey cast iron in order to improve its corrosion resistance, which method is as described above.

[0038] Another object of the invention is to provide a part made of an iron alloy obtainable by the above-mentioned processing method, - a nitride layer on the surface of the iron alloy, the nitride layer comprising a mixed layer containing nitrides; - a phosphating layer comprising a metal phosphate and disposed on and in contact with the nitride layer; In a part comprising: Primarily, the components are characterized in that the metal phosphates contain zinc and / or manganese, as well as iron.

[0039] The invention also relates to a part made of grey cast iron obtainable by the above-mentioned processing method, a nitride layer on the surface of the grey cast iron, the nitride layer comprising a mixed layer containing nitrides; a phosphating layer disposed on and in contact with the nitride layer, the phosphating layer including a metal phosphate; Equipped with It mainly concerns parts characterised in that the metal phosphate comprises zinc and / or manganese, as well as iron.

[0040] Preferably, the phosphorylation layer has a thickness of 3 μm to 40 μm, preferably 5 μm to 30 μm, even more preferably 5 μm to 20 μm.

[0041] Preferably, the mixed layer has a thickness of 5 μm to 40 μm, preferably 15 μm to 25 μm.

[0042] Unless the component has been subjected to prior degraphitization, the component will have graphite inclusions at the surface of the component on which the mixed layer is formed, and these graphite inclusions will be located on at least one surface of the component on which the mixed layer is formed.

[0043] The part is preferably a brake disc. In this case, the phosphating is a zinc / iron phosphating. The invention therefore also relates to a brake disc having the characteristics of the part made of grey cast iron described above.

[0044] Other advantages and features of the invention will appear clearly on reading the following description, given by way of non-limiting example and with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0045] [Figure 1] 1 is a photomicrograph of a part according to an embodiment of the present invention, the part being a brake disc made of lamellar cast iron. [Diagram 2] 2 is a photograph of the part of FIG. 1 after nitriding / phosphating treatment and before salt spray testing. [Diagram 3] 1 is a photograph of a part not according to the invention, which is a brake disc made of lamellar cast iron. [Figure 4] 4 is a photograph of the part of FIG. 3 after nitriding / phosphating treatment and before the salt spray test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] The Applicant's approach is to carry out several series of tests exercising different treatments of a part (P) made of grey cast iron.

[0047] The problem to be addressed consists of finding a way to give a part (P) sufficient corrosion resistance, despite the fact that the nitriding bath does not contain sulfur and, moreover, that said part is made of non-degatized grey cast iron, and therefore corrosion is particularly difficult to prevent.

[0048] The treated parts (P) are subjected to a salt spray and their corrosion resistance is evaluated from the duration of the appearance of pitting and / or the threshold of rust runoff.

[0049] The second problem was then to verify the correct operation of the so treated part (P) according to the specific use of the brake disc, therefore comparative friction coefficient measurements were made.

[0050] In particular, applicants have investigated the effect of two following steps.

[0051] With reference to the micrograph shown in Figure 1, the ARCOR nitriding process (a trademark registered by the applicant) provides a juxtaposed intermixed layer (1) and diffusion zone (1') from the surface to the core of the part (P). The intermixed layer (1), typically having a thickness of 5-30 μm, is formed on the surface of the substrate (S) that constitutes the part (P).

[0052] The diffusion zone (1') typically has a thickness of a few tens or hundreds of microns, for example 300 μm, measured from the surface of the substrate (S) of the component (P) in the direction of the core of said component.

[0053] The nitriding was carried out in a bath of molten salt.

[0054] Phosphating provides a metal phosphate layer (2) on the surface of the part (P) above the mixed layer (1). The metal phosphate layer (2) typically has a thickness of about 20 μm.

[0055] In the micrograph of FIG. 1, an additional layer (a) can be observed: this is an aluminium layer which does not form part of the part (P) but which has been deposited with a view to making the cuts required for the micrograph.

[0056] Furthermore, lamellar-shaped graphite inclusions (G) can be observed, which are open on the surface of the part (P).

[0057] A first series of corrosion protection tests was carried out: a part (P) manufactured as a grey cast iron base and subsequently treated was installed in an enclosure and subjected to a salt spray test.

[0058] The enclosure is then opened every 24 hours to verify the appearance of corrosion spots that provide evidence of the onset of localized corrosion. These spots are counted, and if any of them exceed a predefined threshold, for example 50, the part (P) is considered corroded and the test is stopped.

[0059] The longer it takes to reach the threshold, the more resistant the part is to corrosion. Minimum corrosion resistance has been determined by applicants for a period of 96 hours or greater.

[0060] Table 1 below shows the corrosion tests that are more important to understanding the present invention.

[0061] [Table 1]

[0062] "ARCOR L" nitriding is a ferritic nitrocarburizing process, the treatment temperature can vary between 530 °C and 650 °C, depending on the steel to be treated and the required specifications. It corresponds to that described in document FR 2 972 459. "ARCOR L" nitriding baths contain chloride ions.

[0063] "ARCOR V" nitriding is a ferritic nitrocarburizing process, the treatment temperature can vary between 500°C and 700°C, depending on the steel to be treated and the required specifications. It corresponds to the nitriding part described in document FR2812888. "ARCOR V" nitriding baths do not contain chloride ions.

[0064] The post-treatment "Oxidation 1" is a method of oxidation in a bath of molten salt at a temperature of 450°C.

[0065] The post-treatment "Oxidation 2" is a method of oxidation in an aqueous solution, and the treatment temperature can vary between 120° C. and 140° C. Salts are formed mainly with nitrates, nitrites and carbonates associated with Na+ alkali cation.

[0066] The "Ph(ZnFe)" post-treatment is a method for phosphorylation, and the treatment temperature can vary between 60°C and 70°C. The salt used is (H 2 PO 4 ) 2 Me type, Zn 2+ ions (Me=Zn). The iron is provided in the form of iron powder.

[0067] The "Ph(ZnCa)" post-treatment is a method for phosphorylation, and the treatment temperature can vary between 80°C and 90°C. The salt used is (H 2 PO 4 ) 2 Me type, Zn 2+ and Ca 2+ Contains ions (Me=Zn, Ca).

[0068] The "Ph(Zn)" post-treatment is a method for phosphorylation, and the treatment temperature can vary between 60°C and 70°C. The salt used is (H 2 PO 4 ) 2 Me type, Zn 2+ Contains only ions.

[0069] Based on the corrosion tests carried out, the following conclusions can be drawn:

[0070] With reference to the photograph in FIG. 2, it can be seen that the part according to the invention (P) has no corrosion spots (the photograph was taken at the end of the 48 hour test).

[0071] Referring to the photograph in Figure 3, the part not according to the invention (C14) has a corrosion point (pc) of over 50 at the end of the 48 hour test. Thus, the treatment designated C14 is inadequate.

[0072] With reference to FIG. 4, a micrograph of part (C14) was taken after treatment and before the salt spray test. It is observed that the boundary between the phosphorication layer (2) and the mixed layer (1) is less clear than on the part according to the invention (P). It can be inferred that the deposition of the phosphorication layer (2) attacked the mixed layer (1) in so far as phosphorication with Zn alone removed the Fe ions in the substrate. It is observed that phosphorication with zinc alone on the nitrided part does not provide good corrosion protection, in contrast to a substrate made of zinc-iron phosphoric acid alloy but not subjected to nitriding. This observation leads to theorization that the dissolution of iron from the mixed layer may make the surface of the substrate (S) too rough, which may increase the porosity of the phosphorication layer.

[0073] This phenomenon occurs because the phosphating bath contains Zn 2+ ions and Fe 2+ When ions are included, this is not observed (Test C10).

[0074] From the testing of all the different nitriding and phosphating / oxidation combinations on parts (P) that have not been subjected to degraphitization, only the combination "ARCOR L" nitriding and "Ph(Zn and / or Mn)+Fe" phosphating makes it possible to obtain sufficient corrosion resistance (test C10).

[0075] Other tests were then carried out to verify that the characteristics of the treated part (P) were suitable for use as a brake disc.

[0076] It has been observed that the presence of manganese ions in the phosphating bath gives the part (P) a lower coefficient of friction, which is not compatible with use as a brake disc.

[0077] However, parts (P) that have not been subjected to degraphitization but to "ARCOR L" nitriding and "Ph(ZnFe)" phosphating are perfectly suitable for such use.

[0078] In this respect, the frictional performance of such parts (P) is close to that of the prior art.The method according to the invention is therefore particularly adapted to the treatment of brake discs.

[0079] However, the method according to the invention is cheaper than the prior art solutions since it allows to avoid degraphitization.The nitriding step in particular is cheap since the nitriding salts (chlorides) used are economical and their dosage is not critical.

[0080] In other words, the method according to the invention requires only nitriding and phosphating to modify the chemical nature and macroscopic structure of the part (P) and thus to give it good mechanical properties, in particular mechanical strength, wear resistance and corrosion resistance.

[0081] Furthermore, because both nitridation and phosphating are performed by baths, no re-plating of parts is required to move from one process to another, facilitating industrialization, especially since the time to perform the complete process is generally shorter than that of an equivalent gas-phase nitridation.

[0082] To produce the part (P), other iron-based alloys such as steel or white cast iron could be considered, however grey cast iron is of interest as it is the cheapest material.

Claims

1. A method for treating a part (P) made of an iron alloy in order to improve its corrosion protection and mechanical strength properties, comprising the steps of: - forming a mixed layer (1) on said part (P) by molten salt bath nitriding or molten salt bath nitrocarburizing, and then - phosphorylating said component (P) to form a phosphorylation layer (2) on the surface of said component; Including, The bath of molten salt contains chlorides; 13. A method according to claim 12, characterized in that the phosphating step is carried out in a phosphating bath containing zinc and / or manganese ions, as well as iron ions.

2. The method of claim 1 , wherein the bath of molten salt does not contain sulfur.

3. 3. The method of claim 1 or claim 2, wherein the chloride comprises an alkali metal chloride.

4. 4. The method of claim 3, wherein the alkali metal chloride is lithium chloride, sodium chloride and / or potassium chloride.

5. The bath of molten salt comprises: - 25% to 60% alkali metal chlorides, - 10% to 40% of alkali metal carbonate, - 20% to 50% of an alkali metal cyanate, - Cyanide ions less than 3% Including, 5. The method according to claim 1, wherein the percentages are expressed by weight relative to the total weight of the bath.

6. if the phosphorylation bath contains zinc ions but no manganese ions, the zinc ions are present in a mass concentration of from 1 g / l to 40 g / l, preferably from 5 g / l to 20 g / l, relative to the total volume of the phosphorylation bath; if the phosphorylation bath contains manganese ions but no zinc ions, the manganese ions are present in a mass concentration of from 1 g / l to 40 g / l, preferably from 5 g / l to 20 g / l, relative to the total volume of the phosphorylation bath; if the phosphating bath contains zinc and manganese ions, the sum of these ions is present in a mass concentration of from 1 g / l to 40 g / l, preferably from 5 g / l to 20 g / l; iron ions are in each case present in the phosphorylation bath in a mass concentration of from 1 g / l to 8 g / l, preferably from 1 g / l to 6 g / l and more preferably from 1 g / l to 5 g / l; 6. The method according to any one of claims 1 to 5.

7. The method according to any one of the preceding claims, wherein the phosphorylation layer (2) has a thickness of 3 μm to 40 μm, preferably 5 μm to 30 μm, more preferably 5 μm to 20 μm.

8. The method according to any one of the preceding claims, wherein the mixed layer (1) has a thickness of from 5 μm to 40 μm, preferably from 15 μm to 25 μm.

9. 9. The method according to any one of the preceding claims, wherein the part (P) is made of grey cast iron.

10. A part (P) made of grey cast iron obtainable by a processing method according to any one of claims 1 to 9, a nitrided layer comprising a mixed layer (1) containing nitrides and in contact with grey cast iron; a phosphorylation layer (2) comprising a metal phosphate and arranged on and in contact with said mixed layer (1); Equipped with Component (P), characterized in that the metal phosphate comprises zinc and / or manganese, and iron.

11. Component (P) according to claim 10, wherein said phosphorylation layer (2) has a thickness of between 3 μm and 40 μm, preferably between 5 μm and 30 μm, more preferably between 5 μm and 20 μm.

12. 12. Part (P) according to claim 10 or 11, having graphite inclusions (G) on the surface of the part (P) on which the mixed layer (1) is formed.

13. 13. A part (P) according to any one of claims 10 to 12, wherein the part is a brake disc.

Citation Information

Patent Citations

  • Surface treatment of frictional sliding face

    JP1978001647A

  • Method for treating steel part with phosphate to improve corrosion and wear resistance thereof

    JP1994081165A

  • Molten salt bath and method for nitriding steel machine parts

    JP2014510840A

  • Salt Bath Ferritic Nitrocarburizing of Brake Rotors

    US20080000550A1

  • Braking band of a disk for disk brake

    WO2021124100A1